4x+3(4+x)=-9

Simple and best practice solution for 4x+3(4+x)=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+3(4+x)=-9 equation:


Simplifying
4x + 3(4 + x) = -9
4x + (4 * 3 + x * 3) = -9
4x + (12 + 3x) = -9

Reorder the terms:
12 + 4x + 3x = -9

Combine like terms: 4x + 3x = 7x
12 + 7x = -9

Solving
12 + 7x = -9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 7x = -9 + -12

Combine like terms: 12 + -12 = 0
0 + 7x = -9 + -12
7x = -9 + -12

Combine like terms: -9 + -12 = -21
7x = -21

Divide each side by '7'.
x = -3

Simplifying
x = -3

See similar equations:

| (6x+4)+(15-7)= | | 11z+4z^2+10z^2= | | 265=(x+5)(3x+5) | | 137=5x+6(-3x+12) | | 2f+8-f=3 | | -2(x-3)+3(x+2)=4 | | 5y-2+y+20=8y+20-4y | | 16x+8-8x=32 | | 2x+10-2=2x+4 | | 9*9-3y=-27 | | 2u+5u+2=0 | | 3x^3-x^2-8x-5=0 | | 9*3-3y=-27 | | 3x^2=(x+5)(3x+5) | | 5y-2+y+20=8y+20 | | 45=15*h | | 6X+13= | | 9=b(b-8) | | y+2=0.1y | | 3x^2-x^2-8x-5=0 | | 2(4x+2)-10=74 | | 12a+3+18+9a= | | 1/3(6x-9)=2x-3 | | 86-3X=42X+16 | | 4.5x+(-5)=17 | | 10(1-2(.5))=-5(2(.5)-1) | | 9-10X=53-24X | | p-5.16=15.48 | | 12(2-x)=4-6(x+2) | | 93+-84= | | 10(1-2(1.5))=-5(2(1.5)-1) | | x-4y=48 |

Equations solver categories